Assessment of European Work Councils By Turkish Trade Unions - ErdoÄŸan, Ekrem; Ã–zdemir, Mustafa ÒªaÄŸlar (Mediterranean Journal of Social Sciences, 2012)
This paper aims to present the assessment of the European Work Councils which provide workers with informing andcounselling right by Turkish trade unions. European Union membership process entails to comply with the legal acquis of the EU.Therefore, the effects of the European Work Councils Directive which provide workers with informing and counselling right on Turkishworkers have become an important subject. Turkish workers have the right of participating in decision-making process by trade unions,collective labour bargaining and some methods on work place level. However, the effectiveness of these methods is low as a result ofthe dominant position of the state, negative approach of employers and relative weakness of workers. Moreover, narrow-scopedindustrial relations system which is regulated in detail and the existence of informal economy reduce the effect of these methods.Reviewing labour relations and its legal background in the EU show us that there is a considerable difference according to Turkishindustrial relations. The most significant difference is the participation of all parties in decision making process related to the EUindustrial relations. It can be said that European Social Model (ESM) lie behind the participation culture and the Directives. During recentyears the European Social Model is associated with â€œincreasing economic performance, advanced social protection and social dialogâ€(Hermans, 2005: 5). Right after European Single Market was created; there has been an increase in the number of multinationalcorporations and their interrelations. Multinational corporations consider revising their management structure at national level necessaryaccording to new developments at European Level (Marginson, 1997: 224-225). Therefore, the Council Directive 94/45/EC2 which isrelated to employee participation in decision making process was legislated in 1994 with the intention of maintaining economic relations;reduce competitive pressure between corporations and accordance in management methods. The Council Directive 94/45/EC wasrevised in May 2009 and new Directive 2009/38/EC is in effect. One of the negotiation titles between Turkey and the EU is social policyand employment. The Directive 2009/38/EC is among the subjects in negotiations. In this context, presenting assessments of TurkishTrade Unions on European Work Councils make contribute to the process and to determine reservations on the subject.